Association Between Blood Pressure Variability With Dementia and Cognitive Impairment: A Systematic Review and Meta-Analysis. Issue 5 (November 2021) - de Heus, Rianne A.A.; Tzourio, Christophe; Lee, Emily Jo Lynn; Opozda, Melissa; Vincent, Andrew D.; Anstey, Kaarin J.; Hofman, Albert; Kario, Kazuomi; Lattanzi, Simona; Launer, Lenore J.; Ma, Yuan; Mahajan, Rajiv; et al.
Abstract : Research links high blood pressure variability (BPV) with stroke and cerebrovascular disease, however, its association with cognition remains unclear. Moreover, it remains uncertain which BP-derived parameter (ie, variability or mean) holds more significance in understanding vascular contributions to cognitive impairment. We searched PubMed, Embase, PsycINFO, and Scopus and performed a meta-analysis of studies that quantified the association between resting BPV with dementia or cognitive impairment in adults. Two authors independently reviewed all titles, abstracts, and full-texts and extracted data, following Preferred Reporting Items for Systematic Reviews and Meta-Analyses and Meta-Analysis of Observational Studies in Epidemiology guidelines. Study quality was assessed using the (modified) Newcastle-Ottawa Scale. A multilevel meta-analysis was used, which included effect sizes for both BPV and mean BP, with a combined end point of dementia or cognitive impairment as primary outcome. In the primary analysis, 54 effect sizes were extracted from 20 studies, with a total analytical sample of n=7 899 697. Higher systolic BPV (odds ratio [OR], 1.25 [95% CI, 1.16–1.35]), mean systolic pressure (OR, 1.12 [95% CI, 1.02–1.29]), diastolic BPV (OR, 1.20 [95% CI, 1.12–1.29]), and mean diastolic pressure (OR, 1.16 [95% CI, 1.04–1.29]) were associated with dementia and cognitive impairment. A direct comparison showed that mean BP effect sizes were less strong than BPV effect sizes (OR, 0.92 [95% CI, 0.87–0.97], P <0.01), indicating that the relative contribution of BPV exceeded that of mean BP. Methodological and statistical heterogeneity was high. Secondary analyses were less consistent as to whether BPV and mean BP were differentially associated with dementia subtypes and cognitive domains. Future studies are required to investigate BPV as a target for dementia prevention. Abstract : Supplemental Digital Content is available in the text.